2020
DOI: 10.1103/physrevb.101.064409
|View full text |Cite
|
Sign up to set email alerts
|

Origin and tuning of room-temperature multiferroicity in Fe-doped BaTiO3

Abstract: Simultaneous co-existence of room-temperature(T) ferromagnetism and ferroelectricity in Fe doped BaTiO3 (BTO) is intriguing, as such Fe doping into tetragonal BTO, a room-T ferroelectric (FE), results in the stabilization of its hexagonal polymorph which is FE only below ∼80K. Here, we investigate its origin and show that Fe-doped BTO has a mixed-phase room-temperature multiferroicity, where the ferromagnetism comes from the majority hexagonal phase and a minority tetragonal phase gives rise to the observed we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 52 publications
(41 reference statements)
1
28
0
Order By: Relevance
“…Moreover, theoretical work predicts that Cr-, Mn-, and Fe-doped BTO systems are essentially ferromagnetic and derived from doping atoms. [11] Many subsequent experimental studies since then confirmed the previous predictions, and room temperature FM has been reported in Mn-, [13] Fe-, [14][15][16] and Cr [17] doped BTO system. However, the ME effect of the magnetic element doped BTO system is still small.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, theoretical work predicts that Cr-, Mn-, and Fe-doped BTO systems are essentially ferromagnetic and derived from doping atoms. [11] Many subsequent experimental studies since then confirmed the previous predictions, and room temperature FM has been reported in Mn-, [13] Fe-, [14][15][16] and Cr [17] doped BTO system. However, the ME effect of the magnetic element doped BTO system is still small.…”
Section: Introductionsupporting
confidence: 66%
“…Indeed, one of the most direct ways to achieve room-temperature ME effect is to introduce FM into the ferroelectrics through transition magnetic atom (Cr, Mn, Fe, Co, and Ni) doping. [11][12][13][14][15][16][17] BaTiO 3 (BTO) is one of the most common ferroelectrics used in the synthesis of MFs, with high dielectric constant, low dielectric loss, and lead-free. Moreover, theoretical work predicts that Cr-, Mn-, and Fe-doped BTO systems are essentially ferromagnetic and derived from doping atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Next, to study the intrinsic ferroelectric properties, we have employed the PUND 12,13 technique (for details see ref. 5 ). In Fig.3(a) we see that from x=0 there is a sudden increase in the ferroelectric polarization value for x=0.02 and then it continues to decrease up to x=0.10 [also, refer to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9 and note the discussions in subsection-C of the supplementary material below). Now, to have a holistic view, we have plotted the remanent polarization value (dPr) versus sample tolerance factor (which can strongly influence structural instabilities of such perovskite oxides 15 ) as shown in Fig.3(d), using Fe and Ti valencies determined from the Fe-K edge XANES and XPS spectroscopic studies 5 (for details, refer to subsections E-G and note Fig. 10 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation